A Study on Non Insulin Dependent Diabetes Mellitus (Advancements in Homeopathic Research, 2022)
In this era, where there is enough and more number of diseases, there is a disease that ranks high and has been attacking the human world due to life style derangement since ages – “DIABETES MELLITUS.”
Keywords: Non Insulin Dependent Diabetes Mellitus; Methodology; Management; Homoeopathy